ASUHAN KEPERAWATAN MEDIKAL BEDAH PADA Tn. S DENGAN PENERAPAN RELAKSASI DIAPHRAGMATIC BREATHING EXERCISE PADA PASIEN PARU OBSTRUKTIF KRONIK DI RUMAH SAKIT HARAPAN BUNDA KOTA BATAM - Khoeriyah, Anisatul; Gemini, Savitri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Chronic obstructive pulmonary disease is a progressive lung disease characterized by irreversible airflow obstruction associated with the lung's inflammatory response to particles. The method used in this Professional Scientific Writing is a case study. The results of the assessment showed that the client complained of shortness of breath accompanied by a non-productive cough. The intervention and implementation provided was in the form of the Diaphragmatic Breathing Exercise Relaxation technique for 5 days. Obtained the results of the final evaluation of nursing care for Mr. S with COPD that was obtained after the Nursing Implementation was carried out: The patient said he was no longer short of breath, the patient said there was a change after relaxing the diaphragm breathing, the breathing aid was not installed, the patient looked relaxed, the breathing rhythm was regular, the breathing pattern improved, BP: 112/88 MmHg , N: 97x/minute, RR: 22x/minute, S: 36.5, Spo2: 99% without breathing apparatus. Through the application of Diaphragmatic Breathing Exercises, it is hoped that COPD sufferers can become an appropriate non-pharmacological therapy to improve respiratory frequency, additional breath sounds can be reduced and improve oxygen saturation in COPD patients.Keywords: PPOK, Nursing Care Diaphragma Breathing exercise